National Foresight in Korea: History of Futures Studies and Foresight in Korea. (September 2019) - Heo, Kyungmoo; Seo, Yongseok
Public interests in coming futures of Korea continue to be increasing. Fears on uncertainties and pending challenges as well as demands on a new but Korea-own development model trigger a quantitative increase of futures research and relevant organizations in both public and private. The objective of this paper is to review history of futures studies and national development plan and strategy linked with foresight along with its challenges and recommendations. This paper identifies drawbacks and limits of Korea foresight such as misapplication of foresight as a strategic planning tool for modernization and economic development and its heavy reliance on government-led mid- and long-term planning. As a recommendation, an implementation of participatory and community-based foresight is introduced as a foundation for futures studies in Korea. A newly established research institute, the National Assembly Futures Institute, has to be an institutional passage to deliver opinions of the public, a capacity-building platform to increase the citizen's futures literacy, and a cooperative venue for facilitating a participation and dialogue between politicians, government officials, and researchers.